Microwave Absorption of Crystalline Fe/MnO@C Nanocapsules Embedded in Amorphous Carbon - He, Gaihua; Duan, Yuping; Pang, Huifang (Nano-Micro Letters, 2020)
Crystalline Fe/MnO@C core–shell nanocapsules inlaid in porous amorphous carbon matrix (FMCA) was synthesized successfully with a novel confinement strategy. The heterogeneous Fe/MnO nanocrystals are with approximate single-domain size which gives rise to natural resonance in 2–18 GHz. The addition of MnO2 confines degree of graphitization catalyzed by iron and contributes to the formation of amorphous carbon. The heterogeneous materials composed of crystalline–amorphous structures disperse evenly and its density is significantly reduced on account of porous properties. Meanwhile, adjustable dielectric loss is achieved by interrupting Fe core aggregation and stacking graphene conductive network. The dielectric loss synergistically with magnetic loss endows the FMCA enhanced absorption. The optimal reflection loss (RL) is up to − 45 dB, and the effective bandwidth (RL < − 10 dB) is 5.0 GHz with 2.0 mm thickness. The proposed confinement strategy not only lays the foundation for designing high-performance microwave absorber, but also offers a general duty synthesis method for heterogeneous crystalline–amorphous composites with tunable composition in other fields. Highlights: 1 The crystalline Fe/MnO@C core–shell nanocapsules embedded in porous amorphous carbon matrix (FMCA) was prepared by a novel confinement strategy of modified arc-discharge method. 2 The heterogeneous crystalline–amorphous nanocrystals disperse evenly and exhibit improvement of static magnetization and excellent electromagnetic absorption properties. 3 The adding MnO2 confines degree of graphitization and contributes to form amorphous carbon. Dielectric loss and microwave absorption are achieved adjustable.